Analisis Pengembangan Transportasi Logistik Menggunakan Mode Inland Waterway (Studi Kasus: Kawasan Industri Jababeka) - Saputri, Yunia Eka; Suryobuwono, Abdullah Ade; Sholihah, Sita Aniisah (Jurnal Sistem Transportasi & Logistik, 2023)
The logistics business is one sector of activity that is currently showing a high growth rate, in line with the increasing needs of society and the development of increasingly sophisticated technology. This development must be supported by efforts made to create an effective and efficient logistics system. The main trigger for the high cost of logistics in Indonesia is the inadequate logistics system and infrastructure. Therefore, an effective and efficient mode of transportation is needed in order to achieve optimization of logistics costs for companies, especially in the Cikarang area. The analytical tools used are Multinomial Logistic Regression, Crosstab Analysis and Stated Preference. From this analysis, there are four factors that most influence the willingness of respondents to use canal/waterway-based modes. These factors are the type of goods, the number of goods, shipping costs, and the reason for choosing the mode. Based on the calculation results of the four scenario simulations that have been carried out, it is known that the probability of switching from a highway/truck-based mode to a canal/waterway-based mode is 58.9% switching.